2023
DOI: 10.1186/s12955-022-02086-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbid mental health conditions in people with epilepsy and association with quality of life in low- and middle-income countries: a systematic review and meta-analysis

Abstract: Background Comorbid mental health conditions are common in people with epilepsy and have a significant negative impact on important epilepsy outcomes, although the evidence is mostly from high-income countries. This systematic review aimed to synthesise evidence on the association between comorbid mental health conditions and quality of life and functioning among people with epilepsy living in low- and middle income countries (LMICs). Methods We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…showed that 41.3% of infertile women in Iran had symptoms of post-traumatic stress disorder. This difference may be due to differences in regional development levels and women's rights, as low-income patients with certain diseases were more likely to suffer from mental illness [29]. Shanghai's higher economic level and more openminded residents may be a big factor.…”
Section: Discussionmentioning
confidence: 99%
“…showed that 41.3% of infertile women in Iran had symptoms of post-traumatic stress disorder. This difference may be due to differences in regional development levels and women's rights, as low-income patients with certain diseases were more likely to suffer from mental illness [29]. Shanghai's higher economic level and more openminded residents may be a big factor.…”
Section: Discussionmentioning
confidence: 99%
“…PWEs exercise less frequently compared to the general population, often experiencing a higher likelihood of obesity and lower levels of physical and mental well-being, indicat-ing a proclivity toward inactivity and diminished health [11,12,14]. Conversely, empirical investigations have shown that active participation in exercise improves epileptic seizure control, enhances the quality of life, reduces depression and anxiety, and mitigates the side effects of antiepileptic drugs in PWEs [15].…”
Section: Effects Of Sports On Pwesmentioning
confidence: 99%
“…Because of these restrictions, PWEs engage in physical activity significantly less frequently than the general population [9, 10], leading to higher rates of obesity and diminished physical and mental well-being [11, 12]. These trends underscore the fact that individuals with epilepsy tend to have less active lifestyles and consequently grapple with compromised health.…”
Section: Physical Exercise Restriction In Pwesmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis of 19 studies from low-and middle-income countries (LMICs) also found a signi cant negative association between comorbid depression (pooled effect size (ES) -1.16, 95% CI -1.70, -0.63) or anxiety (pooled ES -0.64, 95% CI -1.14, -0.13) on QoL of people with epilepsy (19).…”
mentioning
confidence: 99%